Efektivitas Berbagai Herbisida dalam Pengendalian Gulma pada Tanaman Menghasilkan di Perkebunan Kelapa Sawit (Elaeis guineensis Jack.) - Ramadhani, Fitri; Yakup, Yakup; Angraeni, Dian Elsi (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2023)
Ramadhani, F., Yakup, Y., Angraeni, D.E. (2023). The effectiveness of different herbicides in controlling weeds in oil palm (Elaeis guineensis Jack.) plantations. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang 21 Oktober 2023. (pp. 570-580). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Oil palm (Elaeis guineensis Jacq.) is one of the most important plantation products in the Indonesian economy. The aimed of this study was to identify the effective herbicide for oil palm farms. Research has been carried out From November 2022 to February 2023, in PT Intimegah Bestari Pertiwi in Kemang, Sanga Desa District, Musi Banyuasin Regency, Indonesia. The method used in this research was randomized block design (RBD) and there were 10 treatments which were repeated three replications. The results showed that herbicide treatment had a significant effect on weed dry weight at 4 MSA, but not at 8 MSA or 12 MSA, according to analysis of variance. Weed vegetation was analyzed before application and the results showed that there were 4 grass weed species, 7 broadleaf weed species and 1 puzzle weed species. The Sum Dominance Ranking (SDR) of the weeds varied. Weeds with SDR more than 5% are revealed by the study, namely in the group of herbaceous leaf weeds there was 1 species namely Ottochloa nodosa 38.4%, in the group of broadleaf weeds there were 3 species namely Clidemia hirta 12.3%, Legazpia polygonoides Beth 10.6%, Borreria alata 6.41%, Melastoma candidum L. 6.14%. thus, there is 1 species of weeds in the puzzle type namely Scleria sumatrensis 9.59%. and based on direct visual observations in the field, the use of herbicides in each treatment showed 0 or no symptoms of poisoning (toxic) to oil palm plants.